Online Media and Establishment of Religious Understanding of the Madrasah Aliyah Students in Gorontalo - Arafah, Sitti; Basman, Basman; Nisa’ , Khaerun; Abubakar, Asnandar (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
This research is a qualitative descriptive study that aims to describe the religious understanding of Madrasah Aliyah (MA) students in Gorontalo obtained from online media. It was also conducted to determine the school's response in harmonizing religious understanding. This study aims to answer the following questions: (1) How is the religious understanding of Madrasah Aliyah students obtained through online media? and (2) How do the schools respond and harmonize the religious understanding of students who interact with online religious sites? Data were collected through observation, interviews, and documents study, by targeting Madrasah Aliyah students, teachers, religious leaders, academics, and community leaders. The results showed that MA students use online media as sources of learning materials and religious content with the duration of accessing online media reaching 4 to 10 hours per day. It has influenced the understanding, attitudes, and religious practices of MA students. The understanding and practice of